Respuesta :

Answer:

X=6

Step-by-step explanation:

5(x+2)=6x+3x−1

Step 1: Simplify both sides of the equation.

5(x+2)=6x+3x−14

(5)(x)+(5)(2)=6x+3x+−14(Distribute)

5x+10=6x+3x+−14

5x+10=(6x+3x)+(−14)(Combine Like Terms)

5x+10=9x+−14

5x+10=9x−14

Step 2: Subtract 9x from both sides.

5x+10−9x=9x−14−9x

−4x+10=−14

Step 3: Subtract 10 from both sides.

−4x+10−10=−14−10

−4x=−24

Step 4: Divide both sides by -4.

−4x / -4= −24 / −4

x=6

Answer:

[tex]x=6[/tex]

Step-by-step explanation:-

____________________

[tex]5\left(x+2\right)=6x+3x-14[/tex]

First, we will Add smiler elements: [tex]6x+3x=9x[/tex]

[tex]5\left(x+2\right)=9x-14[/tex]

Expand [tex]5(x+2)[/tex] by applying Distributive law: [tex]a(b+c)=ab+ac[/tex]

[tex]5x+5\times \:2[/tex]

[tex]5x+10[/tex]

[tex]5x+10=9x-14[/tex]

Now, Subtract 10 from both sides :

[tex]5x+10-10=9x-14-10[/tex]

[tex]-4x=-24[/tex]

Divide both sides by - 4:

[tex]\frac{-4x}{-4}=\frac{-24}{-4}[/tex]

[tex]x=6[/tex]

__________________

OAmalOHopeO

ACCESS MORE